2022
DOI: 10.1101/2022.05.02.490306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of the investigational drug sodium phenylbutyrate-TUDCA (AMX0035) on the transcriptional and metabolic landscape of sporadic ALS fibroblasts

Abstract: ALS is a rapidly progressive, fatal disorder caused by motor neuron degeneration, for which there is a great unmet therapeutic need. AMX0035, a combination of sodium phenylbutyrate (PB) and taurursodiol (TUDCA, Turso), has shown promising results in early ALS clinical trials, but its mechanisms of action remain to be elucidated. To obtain an unbiased landscape of AMX0035 effects we investigated the transcriptomic and metabolomic profiles of primary skin fibroblasts from sporadic ALS patients and healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…One of the two studies identified a group of patients categorized as “responders” [ 147 ]. Further studies, such as the clinical trial on low dose interleukin 2 (NCT02059759) and the AMX0035 trial, also tried to identify the molecular profiles of these so called “responders” [ 148 , 149 ]. Of course, the identification of responders would be specific to every single treatment, while cluster identification might be suitable for a more generalized usage.…”
Section: Discussionmentioning
confidence: 99%
“…One of the two studies identified a group of patients categorized as “responders” [ 147 ]. Further studies, such as the clinical trial on low dose interleukin 2 (NCT02059759) and the AMX0035 trial, also tried to identify the molecular profiles of these so called “responders” [ 148 , 149 ]. Of course, the identification of responders would be specific to every single treatment, while cluster identification might be suitable for a more generalized usage.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the drug's exact mechanism of action is not well understood. Though it is unknown how the drug exerts its therapeutic effect, it has been established that these two compounds work in conjunction to prevent nerve cell death by inhibiting stress signals within the cell's mitochondria and endoplasmic reticulum [17] . Taurursodiol alone is commonly used to treat chronic cholestatic liver diseases and gallstones due to its anti-apoptotic effects, which includes regulating the expression of specific targets of apoptosis and mitochondrial membrane stabilization [18] .…”
Section: Relyvriomentioning
confidence: 99%
“…The synthesis of the target molecules proceeds from commercially-available benzoic acids 22 or 23, which are first converted to the acid chloride before reaction with a library of synthetic-or commercially-derived anilines and benzyl amines (24)(25)(26)(27)(28)(29)(30)(31) to afford the iodoamide intermediates (32)(33)(34)(35)(36)(37)(38)(39)(40) in high yields without the need for purification (Scheme 3). The target ebselen analogues (19 and 41-48) were prepared by a copper catalyzed ring closing reaction of the iodoamide intermediates (32)(33)(34)(35)(36)(37)(38)(39)(40) in the presence of selenium powder. 73 The stabilizing effects of the molecules were measured against a SOD1 A4V/C6S double mutant in the DSF assay and the protein melting temperature differential (ΔT m ) was used to determine the change in thermal stability of the mutant SOD1 compared to that of the SMC-treated mutant SOD1.…”
Section: Selenium Heterocyclic-based Compounds With Therapeutic Poten...mentioning
confidence: 99%
“…Although the exact mechanism of action of this coformulation is unknown, preclinical studies suggest that both drugs act as chemical chaperones preventing misfolded protein formation and reduce endoplasmic reticulum (ER) stress. 38,39 The most common adverse events occurring in ≥5% of sodium phenylbutyrate/ taurursodiol coformulation recipients include diarrhoea, abdominal pain, nausea, constipation, fatigue, decreased appetite and dizziness. 40 Given that about 350,000 people are diagnosed with ALS worldwide annually 41 (about 15,000 people in the United States), there is an urgent need to discover new and effective therapies for its treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation